Risky business: an analysis of claimsmaking in the development of an Ontario drinking water objective for Tritium - McMullan, Colin; Eyles, John (1999)
On December 22, 1994, the Minister of Environment and Energy for Ontario announced an interim Ontario drinking water objective for tritium (a radioactive waste product released into drinking water supplies during nuclear power production) of 7,000 Bq/L. The Minister's decision overrode the advice of his own advisory committee which had recommended a much lower level (100 Bq/L). Concerns have surfaced with respect to the potential adverse health effects associated with long-term exposure to low doses of tritium, though much uncertainty remains. This paper explores the struggle over the interpretation of the tritium `problem' as claimsmaking in the context of the social construction of risk. Specifically, the paper documents how coalitions in the dispute constructed and communicated the risks associated with tritium in drinking water through the use of identifiable rhetorical idioms and claimsmaking styles that reflect, reinforce, and legitimize their contrasting core values and interests. The coalitions also adopt fundamentally contrasting risk assessment methods. Using excerpts from public hearings on the issue, the paper explores use of risk as a rhetorical resource through an examination of the contrasting risk assessment paradigms adopted by rival coalitions. Such analysis can contribute to our understanding of the use of scientific information in debates over contentious social problems. - Reproduced
Keywords: Drinking water